Studies on Survey of Fusarium wilt of Pea (Pisum sativum L.) and its Management by Native Trichoderma Isolates and Commercial Trichoderma under Pot Condition in Manipur - N, Kripalini; Biswas, Mohan Kumar; Devi, Ph. Sobita; Sinha, Bireshwar (International Journal of Bio-resource and Stress Management, 2018)
A detailed survey was conducted for disease incidence of pea wilt at seven pea growing districts of Manipur viz., Imphal East, Imphal West, Thoubal, Senapati, Ukhrul, Tamenglong and Bishnupur during 2014-2015. The highest disease incidence was found in Litan of Ukhrul district (39.50%) and lowest was found at Toubul of Bishnupur district (10.70%). Under pot experiment, efficacy of four native Trichoderma isolates i.e., TIE-1 TBI-2, TIW-1, TSE-1 and two commercial Trichodema spp. viz T. viride and T. hamatum of seed, soil and seed plus soil treatment against wilt of pea showed reduction in disease incidence. Among the different treatments seed+soil treatment was found better than the soil and seed treatment alone. The highest germination percentage was observed in isolate TIE-1 of seed (60%), soil (66.60%) and seed+soil treatment (80.20%) and lowest germination percentage was observed in commercial T. hamatum of seed (53.60%), soil (60.00%) and seed+soil treatment (65.00%). Disease incidence of four native Trichoderma isolates and two commercial Trichoderma were found nil in 30 DAS. In 60 DAS the highest disease incidence was found in commercial T. hamatum in seed treatment (20.00%) and lowest disease incidence was found in native Trichoderma TSE-1 of seed+soil treatment (2.50%) whereas in 90 DAS highest disease incidence was also found in T. hamatum in soil treatment (40.00%) and lowest disease incidence was found in native Trichoderma isolate TIE-1 of seed+soil treatment (10.66%).The highest plant height was recorded in seed+soil treatment of isolate TBI-2 (70.28 cm at 90 DAS). However in seed+soil treatment of Trichoderma isolate TIE-1 recorded the highest plant canopy (2085.03 cm2 at 90 DAS) no. of pods plant-1 (5.34) and yield (6.91 g pot-1).